Relief of p53-mediated transcriptional repression by the adenovirus E1B 19-kDa protein or the cellular Bcl-2 protein. - Shen, Y (1994)
The p53 tumor suppressor gene product is a transcriptional regulatory protein. It activates transcription from promoters that contain a p53 DNA binding site but represses many promoters that lack its binding site. High-level expression of wild-type p53 can induce apoptosis in certain cell types, and this activity can be blocked by the adenovirus E1B 19-kDa oncoprotein or by the cellular Bcl-2 oncoprotein. Here we report that p53-mediated repression of promoters that lack a p53 binding site is abrogated by the E1B 19-kDa protein or Bcl-2 oncoprotein. In contrast, transcriptional activation by p53 still occurs in the presence of either protein. The fact that two oncoproteins capable of preventing p53-mediated apoptosis also block transcriptional repression by p53 raises the possibility that p53 might induce apoptosis, at least in part, by repressing transcription.